Neutral Taila Content Study of Dasmula Taila - Saxena, R.B. (Asian Journal of Chemistry, 2010)
A study on neutral taila content (NTC) property of Dasmula taila was undertaken. The NTC values of tila taila, murchhita tila taila and Dasmula taila are found to be 95.56, 95.91 and 93.94% respectively. Medicinal values of Dasmula taila have also been determined in different times and packets.